A commentary on the HC division’s ruling to demolish BGMEA building - Jalil, Md. Abdul (SonarBangladesh.com, 2011)
On 3rd March 2011, the High Court Division of the Supreme Court of Bangladesh has ruled to demolish BGMEA building erected on Hatirjheel lake in Dhaka for illegally constructing this building. This building was erected in 1998 without taking approval from the RAJUK and by violating provisions of three legislation's, such as (a) Wet lands Protection Act 2000; (b) State Acquisition and Tenancy Act 2000; and (c) Building Construction Act 1952. Under these Acts BGMEA authority has committed fraud to get the land and to erect the building on it for which section 6(3) of the Wetlands Protection Act 2000 provides 5 (five) years imprisonment or fine or both against the BGMEA authority and other people involved in the process.